(untitled) (Modern information system and technologies, 2018)
The analysis of modern approaches to site development is carried out and technologies are selected for creating a software service for a laboratory for the collection of medical analyzes Keywords: PHPStorm, data bases, refactoring, HTML, CSS, PHP, JavaScript, development, block diagram